Competition of the informed: Does the presence of short sellers affect insider selling? - MASSA, Massimo (Institutional Knowledge at Singapore Management University, 2015)
We study how the presence of short sellers affects the incentives of the insiders to trade on negative information. We show it induces insiders to sell more (shares from their existing stakes) and trade faster to preempt the potential competition from short sellers. An experiment and instrumental variable analysis confirm this causal relationship. The effects are stronger for "opportunistic" (i.e., more informed) insider trades and when short sellers' attention is high. Return predictability of insider sales only occurs in stocks with high short-selling potential, suggesting that short sellers indirectly enhance the speed of information dissemination by accelerating trading by insiders. (C) 2015 Elsevier B.V. All rights reserved.